Surface Plasmon Resonance (Spr) Sensor Simulation with Kretschmann Configuration Based on Chitosan-Graphene Oxide Nanocomposite for Lead Metal Ion Detection - Novitasari, Desy; Widayanti (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2022)
The presence of metal ions in river water can have a negative impact on humans when consumed. The detection of metal ions is crucial, and one of the methods is the surface plasmon resonance (SPR) phenomenon using SPR sensor system. SPR biosensor system can be used for metal ion deteection, offering advantages such of affordability and rapid detection. This research aims to investigate the influence of adding chitosan-graphene oxide (CS-GO) nanocomposites to SPR sensors as lead ion detectors. The CS-GO nanocomposites is used as a detector with variations in volume fraction and thickness to find the optimum values. The varied volume fractions are 18 nm, 20 nm and 25 nm. The involvement of the CS_GO nanocomposites is demonstrated through the reflectance curve, showing the SPR angle and reflectance values. The Winspall simulator is used to display the reflectance curve. The SPR system utulized a He-Ne laser with a wavelength of 632,8 nm, a BK7 half cylinder prism, and a thin film of silver metal layer. The SPR sensor configuration used is the Kretschmann configuration. The layer system models include BK7 prism/Ag thin film/chitosan/lead ion, and BK7/Ag thin film/CS-GO/lead ion. The nanocomposite CS-GO’s pernittivity is calculated using the Maxwell Garnett effective medium theory. Result show that the refractive index and permittivity values of the CS-GO nanocomposite increase with the increasing volume fraction. The nanocomposite with a volume fraction of 0,099 produce a permittivity of 2,4337 and a refractive index of 1,5600.Larger permittivity values and thicknesses of the nanocomposite also lead to a shift in the SPR angle in the reflectance curve. The most significant SPR angle shift is observed with the use of CS-GO nanocomposite with a volume fraction of 0,099 and a thickness of 25 nm